Effects of non-uniform porosity on thermochemical performance of solar driven methane reforming. (15th January 2020) - Wang, Fuqiang; Shi, Xuhang; Zhang, Chuanxin; Cheng, Ziming; Chen, Xue
Abstract: As one of the effective methods for solving the greenhouse problem, methane reforming has received increasing attention. The performance of a reactor is strongly influenced by the foam structure with different parameters. In this study, the idea of non-uniform partition design of porosity (an expansion kind of hierarchical porous structure) in a porous media reactor was put forward and investigated. The heat and mass transfer phenomena and thermochemical properties of methane reforming under high convergence solar radiation were numerically studied. Finite volume method coupled with thermochemical kinetics is considered to solve this problem. Based on a constant pore size, the porosity of the porous medium is divided into two layers and combined in different forms in an axial direction. The effects of non-uniform porosity on thermochemical performance of solar driven methane reforming are analyzed and an optimization method for non-uniform porosity is proposed. The results show that methane conversion in a reactor with uniform porous media increases with growth up of the porosity. In addition, a reactor with non-uniform porous media exhibits better thermochemical performance and reforming performance compared to one with uniform porous media. Finally, different non-uniform partitions have an impact on methane conversion. When the porosity is constant, methane conversion decreases with an increase of the length of the first layer of porous media, and the maximum methane conversion (82.42%) was achieved at L 1 = 0.01 m with φ1 = 0.75, φ2 = 0.9. Highlights: Finite volume method with reaction kinetics is developed to analyze the methane reforming process. Methane reforming in solar foam reactor with non-uniform porosity is studied. Methane conversion in reactor with uniform porous media increases with porosity. Different non-uniform partitions have a certain impact on the methane conversion.